2011
DOI: 10.4061/2011/621839
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Thyroglobulin Measurement in Diagnosis of Neck Metastases of Differentiated Thyroid Carcinoma

Abstract: Aim. Enlarged cervical lymph nodes (LNs) in patients with thyroid cancer are usually assessed by fine-needle aspiration cytology (FNAC). Thyroglobulin (Tg) is frequently elevated in malignant FNAC needle wash specimens (FNAC-Tg). The objectives of the study were to (1) determine an appropriate diagnostic cut-off for FNAC-Tg levels (2) compare FNAC and FNAC-Tg results in a group of 108 patients affected by differentiated thyroid carcinoma (DTC). Methods. A total of 126 consecutive FNACs were performed on enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
3
18
0
2
Order By: Relevance
“…One prior report suggested that the most appropriate cutoff value of FNA-Tg is 1.1 ng/mL, 12 and another study yielded a cutoff value of 5 ng/mL. 13 The result of our study, 1.8 ng/mL, was between the 2 reports.…”
Section: Discussionsupporting
confidence: 53%
“…One prior report suggested that the most appropriate cutoff value of FNA-Tg is 1.1 ng/mL, 12 and another study yielded a cutoff value of 5 ng/mL. 13 The result of our study, 1.8 ng/mL, was between the 2 reports.…”
Section: Discussionsupporting
confidence: 53%
“…Snozek and colleagues [19] measured FNA-Tg in 122 samples from 88 athyreotic DTC patients, using immunochemiluminometric assay (CLIA) with functional sensitivity of 0.1 μg/L; 50/52 nonmalignant samples (96.2%) had values ≤ 1 μg/L and 70/70 malignant lesions had levels > 1 μg/L. By a different high-sensitivity immunoradiometric assay (IRMA) (functional sensitivity 0.2 μg/L) and adopting a ROC derived cutoff of 1.1 μg/L, the authors of the present review obtained 100% sensitivity, specificity, and accuracy [34]. These results were subsequently confirmed in a large-scale study including 528 cases of FNA-Tg patients [24].…”
Section: Clinical Data From Literaturementioning
confidence: 98%
“…It is used for both lymph nodes and thyroid bed nodules. The recommendations to add TG-W testing to FNA cytology are based on strong evidence of increased sensitivity of combined testing over cytology alone [2,6,8,10,12,14]. Positive FNA cytology in cervical lymph nodes at the time of initial investigation for DTC will necessitate the extension of the surgery to include the involved group of lymph nodes [1].…”
Section: Discussionmentioning
confidence: 99%